2016
DOI: 10.4103/0970-0218.170967
|View full text |Cite
|
Sign up to set email alerts
|

Work-related neck pain among desk job workers of tertiary care hospital in New Delhi, India: Burden and determinants

Abstract: Background:Work-related Neck Pain (WRNP) is a leading cause of disability and absenteeism. There is dearth of information about burden and determinants of WRNP in health facility setting in India.Materials and Methods:A cross-sectional study was carried out at tertiary care hospital in New Delhi. All Group C desk job workers involved in the administrative work were included in the study. Participants were screened for WRNP by using pretested semi-structured questionnaire. Detailed information on probable risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…According to the present study, one-year prevalence of MSDs was highest in lower back (55.5%), followed by neck (48.2%); and the lowest in ankles (4.5%). The findings of this study were consistent with that of similar studies done by Darivemula et al, Mohammadipour et al and Das et al [3][4][5] However, there was no significant association found between gender and musculoskeletal disorders nor age and MSDs. The difference in result between the studies could be due to differences in study populations, working posture, different ergonomic settings and duration of job hours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the present study, one-year prevalence of MSDs was highest in lower back (55.5%), followed by neck (48.2%); and the lowest in ankles (4.5%). The findings of this study were consistent with that of similar studies done by Darivemula et al, Mohammadipour et al and Das et al [3][4][5] However, there was no significant association found between gender and musculoskeletal disorders nor age and MSDs. The difference in result between the studies could be due to differences in study populations, working posture, different ergonomic settings and duration of job hours.…”
Section: Discussionsupporting
confidence: 92%
“…Predesigned semi-structured Questionnaire for sociodemographic details, medical history, computer use, work hours etc inspired from existing literature. [3][4][5] Standardized nordic musculoskeletal questionnaire was used to assess musculoskeletal problems. 6,7 National Institute of Health (NIH), checklist for workstation ergonomics assessment.…”
Section: Study Toolsmentioning
confidence: 99%
“…Esse resultado foi semelhante a outros estudos brasileiros realizados com diferentes classes trabalhadoras como, por exemplo, o realizado com enfermeiros 38 e servidores públicos. 39 Também foram encontrados resultados semelhantes em estudos internacionais, como o realizado na Índia com trabalhadores de um hospital 40 e na Holanda 41 em estudo de coorte realizado também com trabalhadores industriários. Esses resultados mostram uma relação positiva entre a idade avançada e o absenteísmo, que pode ser justificado pelo processo de envelhecimento, o qual acarreta maior fragilidade do organismo e vulnerabilidade às doenças, diminuindo assim, a capacidade funcional do indivíduo.…”
Section: Tabelaunclassified
“…[ 2 ] Work-related neck pain (WRNP) among female desk-job workers is higher than males due to computer usage exceeding 4–6 hours. [ 3 ] Musculoskeletal disorders (MSDs) and other occupational health problems are frequent because of more manual work and unergonomic designing of tools and workplaces. The ergonomic intervention can be a gamechanger to improve the wellbeing of workers which is ultimately beneficial in their productivity, revenue generation, and reducing the rejection cost.…”
Section: Introductionmentioning
confidence: 99%